chemistry

posted by .

2Al(S)+3H2O(g)---->Al2O3(s)+6H2(g)

A.) what is the correct equilibrium expression?

  • chemistry -

    Keq = (H2)^6/(H2O)^3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Chemistry

    Calculate the enthalpy change (delta H) in kJ for the following reaction. 2Al(s) + Fe2O3 (s) ==> 2 Fe(s) + Al2O3(s) use enthalpy changes for the combustion of aluminum and iron. 2Al(s) + 3/2 O2(g) ==> Al2O3(s) Delta H: -1669.8 …
  2. Chemistry

    Calculate the enthalpy change (delta H) in kJ for the following reaction. 2Al(s) + Fe2O3 (s) ==> 2 Fe(s) + Al2O3(s) use enthalpy changes for the combustion of aluminum and iron. 2Al(s) + 3/2 O2(g) ==> Al2O3(s) Delta H: -1669.8 …
  3. Chemistry :(

    Given that: 2Al(s)+(3/2)O2(g)--->Al2O3(s) change in H(rxn)= -1601 kJ/mol 2Fe(s)+(3/2)O2(g)--->Fe2O3(s) change in H(rxn)= -821 kJ/mol Calculate the standard enthalpy change for the following reaction: 2Al(s)+Fe2O3(s)--->2Fe(s)+Al2O3(s) …
  4. Chemistry-College

    Given that: 2Al(s)+(3/2)O2(g)--->Al2O3(s) change in H(rxn)= -1601 kJ/mol 2Fe(s)+(3/2)O2(g)--->Fe2O3(s) change in H(rxn)= -821 kJ/mol Calculate the standard enthalpy change for the following reaction: 2Al(s)+Fe2O3(s)--->2Fe(s)+Al2O3(s) …
  5. chemistry

    balance: Al(s)+H2O(g)--->Al2O3(s)+H2(g) what is the correct equilibrium expression?
  6. chemistry

    balance:Al(s)+H2O(g)--->Al2O3(s)+H2(g) what is the correct equilibrium expression?
  7. chemistry

    how many molecules of h2o if formed from this equation Al2O3 + 3H2 ->2Al + 3H2O
  8. chemistry

    Find the mass of AlCl3 that is produced when 10.0 grams of Al2O3 react with 25.0 g of HCl according to the following equation. Al2O3(s) + 6HCl(aq) → 2AlCl3(aq) + 3H2O(aq) 65.4 g help me ASAP.PLIS..
  9. Chemistry

    Consider the reaction: Fe2O3+2Al=Al2O3 How many grams of Al are necessary to make 100.2 grams of Al2O3?
  10. Chemistry

    Given ∆Hºrxn = -1670 kJ/mol for 2Al(s) + (3/2)O2(g) --> Al2O3(s), determine ∆Hº for the reaction 2Al2O3(s) --> 4Al(s) + 3O2(g). I flipped Al(s) + (3/2)O2(g) --> Al2O3(s) to Al2O3(s) --> A(g) + (3/2)O2(s) and multiplied …

More Similar Questions